Reaction kinetic study of nonthermal plasma continuous degradation of acetone in a closed-loop reactor. (June 2020) - Li, Xueshuang; Li, Man; Peng, Zhen; Zheng, Kewen; Xu, Li; Dong, Junguo; Ren, Guofa; Cheng, Ping
Abstract: Nonthermal plasma (NTP) degradation has been shown to be a promising method for volatile organic compounds (VOCs) removal from air. However, there have been few studies on the degradation of indoor VOCs using NTP, and even less on their reaction kinetics. In this study, NTP degradation of acetone, a representative of oxygenated VOCs, in a closed-loop reactor operating in recirculation mode was investigated. Acetone and organic by-products were characterized in real-time by proton transfer reaction time-of-flight mass spectrometry. The results showed that approximately 85.7% of the acetone degraded within 7.5 h with dielectric barrier discharge treatment at 4.3 W. Methanol, acetaldehyde, formic acid, and acetic acid were observed to be the main organic byproducts with concentrations time-dependent on the order of ppb/ppm. The concentrations of the inorganic by-products O3 and NO2 are also time-dependent and can decrease to nearly 0 after a sufficient degradation time. Based on the concentration measurement in real-time, several rate laws were used to fit the concentration variations of acetone and the organic by-products, and it was observed that they strictly followed the simple kinetic reaction rate laws: acetone followed the first-order rate law, and formic acid formation followed the one-half-order rate law, etc. This study provides a good example of characterizing NTP removal of VOCs in airtight spaces and has important theoretical and practical significance in designing a better NTP device, predicting NTP degradation reaction rate, and accelerating the practical application of NTP technology for indoor air treatment. Graphical abstract: Image 1 Highlights: NTP continuous degradation of acetone was investigated in a closed-loop reactor. A home-made PTR-TOFMS was used to quantify acetone and its organic by-products in real-time. Variations of acetone and the organic by-products strictly follow the kinetic reaction rate laws.